TRADISI MEGANTUNG ARI-ARI (PLACENTA) DI DESA ADAT PEKRAMAN TRUNYAN KINTAMANI BANGLI - Yasa, I Nyoman Kartika (Widyadari: Jurnal Pendidikan, 2019)
In general, the community maintains the placenta after the mother gives birth to the baby in the front door of the house, Namu to the Pekraman Trunyan traditional village community after the mother gives birth to the baby, Ari-ari (Placenta) is hung on a wooden tree branch in one of the Tantanbuni places .         The theory used to dissect the problem The unique tradition of hanging Ari-ari (placenta) is the Sociological Theory of Herbert Spencer with the functional Structural Theory and the Principle Theory of Religion by Kuentjaraningrat. Data were collected by observation, interview and document documents.         Based on the results of the study revealed that, the background factors in the beliefs and beliefs of the people of Trunyan Village were received from their ancestors since the descent "Ida Ratu Puserin Jagat" to Earth, Not permitted to pollute the earth (Trunyan Village Land) with the intention of maintaining the sanctity of the earth or land of Trunyan Village. As for the process of maintaining the Arienta (Placenta) after the mother gives birth to one of the places of Tantanbuni, after the placenta is inserted into the coconut shell which is halved by filling the equipment inside and then closed and hung on a wooden tree branch in Tantanbuni. The meaning contained in announcing and begging for the face of "Sang Hyang Akasa" (God of Heaven) Receiving and approving at the same time giving protection and safety to the Baby.